The isolation and amplification of full length cDNA of oleosins from oil palm (Elaeis guineensis Jacq.) - Jamek, Shariza; Ngoh, Gek Cheng; Chuah, Teong Guan (Academic Journals, 2010)
This study focused on the isolation and amplification of the cDNA clone of oleosin from oil palm. The oil palm cDNA library constructed from the kernel tissues 10 weeks after anthesis (WAA) produced a clone of pO1A containing partial 563 bp sequence of oleosin. The polymerase chain reaction for the rapid amplification of cDNA ends (RACE-PCR) was performed to obtain full length cDNA of oleosin from the RNA transcripts using forward gene-specific primers that is, primer Oleo 3. The product was then cloned into pCR 4 TOPO vector and subjected to sequencing using M13 forward and reverse primers. The end-to-end PCR method was performed to amplify the complete cDNA sequence of oleosin and it produce a 750 bp PCR product. The BLAST results showed that the cDNA from oil palm kernel isolated exhibited high similarities with low molecular weight isoforms of oleosin cDNA from crops like rice, maize and barley.